Is the adjuvanted influenza vaccine more effective than the trivalent inactivated vaccine in the elderly population? Results of a case–control study - Spadea, A.; Unim, B.; Colamesta, V.; Meneghini, A.; D’Amici, A.M.; Giudiceandrea, B.; La Torre, G. (Vaccine, 2014)
Influenza illness is an important public health problem and annual vaccination is globally recommended for high risk populations. The aim was to evaluate and compare the effectiveness of influenza vaccines in reducing hospitalizations for influenza or pneumonia during two influenza seasons in the elderly. A case–control study was performed, using administrative database of the Local Health Unit Roma-A (LHU RM-A). The included subjects were at least 65 years old and residing in one of the four districts of the LHU. The cases were hospitalized for influenza or pneumonia during influenza season in the years 2010–2011 and 2011–2012. The controls were hospitalized in the same period, but not for influenza or pneumonia. The subjects were immunized with the trivalent inactivated influenza vaccine (TIV) in the first influenza season (2010–2011) and with the adjuvanted influenza vaccine MF59 (ATIV) in the second season (2011–2012). A total of 269 cases and 1247 controls were included for the 2010–2011 influenza season, and 365 cases and 1227 controls were selected for the 2011–2012 season. Up to 63.6% cases and 53.5% controls in the 2010–2011 season and 78.6% of cases and 64.1% of controls in the 2011–2012 season have not been vaccinated. Female gender and high educational level were protective factors for hospitalization. Subjects over 75 years were at high risk of hospitalization compared to 65–74 years olds. Influenza vaccination reduced significantly hospitalization in both seasons. In subjects with 65–74 years TIV was more effective than ATIV; vice versa for those over 75 years old. TIV and ATIV reduce hospitalization for influenza or pneumonia with a variable degree of protection in different age groups. In particular, ATIV is more effective in individuals over 75 years old.